Postoperative imaging surveillance for hepatocellular carcinoma: How much is enough?. Issue 7 (17th February 2021) - Mirdad, Rayyan S.; Madison Hyer, J.; Diaz, Adrian; Tsilimigras, Diamantis I.; Azap, Rosevine A.; Paro, Alessandro; Pawlik, Timothy M.
Abstract: Background: The objective of the current study was to define trends in postoperative surveillance imaging following liver‐directed treatment of hepatocellular carcinoma (HCC), and characterize the impact of high‐intensity surveillance on long‐term survival. Methods: Patients who underwent liver‐ directed therapy for HCC between 2004 and 2016 were identified using the SEER‐Medicare database. Trends in surveillance intensity over time, factors associated with high surveillance intensity and the impact of surveillance on long‐term outcomes were examined. Results: Utilization of high‐intensity surveillance abdominal imaging (≥6 scans over 2 years) following liver‐directed therapy of HCC decreased over time (2004–2007: n = 130, 36.1% vs. 2008–2011: n = 181, 29.5% vs. 2012–2016: n = 111, 24.5%; ptrend < 0.001). History of chronic viral hepatitis (hepatitis B: odds ratio [OR], 1.98; 95% confidence interval [CI]: 1.15–3.43; hepatitis C: OR, 1.79; 95% CI: 1.32–2.43), presence of regional (vs. local‐only) disease (OR, 1.47; 95% CI: 1.09–1.98) and receipt of transplantation (OR, 2.23; 95% CI: 1.57–3.17) were associated with higher odds of high intensity surveillance. Intensity of surveillance imaging was not associated with long‐term survival (5‐year overall survival: low‐intensity, 48.1% vs. high‐intensity, 48.9%; hazards ratio, 0.94; 95% CI: 0.78‐1.13). Conclusion: Utilization of posttreatment surveillance imaging decreased over time following liver‐directed therapy for HCC. While utilization of high‐intensity screening varied by HCC procedure performed, intensity of surveillance had no effect on survival.